Salivary oxytocin responses to infant stimuli vary by EPDS scores among postpartum Japanese mothers without clinically diagnosed postpartum depression - Minami, Kana; Higashida, Haruhiro; Yokoyama, Shigeru; Tsuji, Takahiro; Kagami, Naomi; Tsuji, Chiharu (Frontiers in Endocrinology, 2025)
Postpartum depression (PPD) significantly impacts both mothers and children, so its early detection is crucial to mitigate these effects. The Edinburgh Postnatal Depression Scale (EPDS) is a widely used screening tool for identifying individuals at risk of PPD. However, PPD symptoms often emerge gradually, and subtle changes in maternal well-being within the low-risk EPDS range may be overlooked. Oxytocin (OT), a neuropeptide important for social functioning and maternal behaviors, may offer deeper insights into the progression of PPD. This exploratory cross-sectional study examined the association between EPDS scores and salivary OT responses to infant-related stimuli in postpartum Japanese mothers without PPD diagnosis. We hypothesized that OT responses would differ according to mothers’ EPDS scores, with higher scores associated with blunted OT reactivity. OT responses were assessed within one year postpartum under breastfeeding, interaction, or video tests. Mothers with EPDS <5 showed increased OT responses, whereas those with ≥5 showed diminished responses. The difference in OT responses observed below the EPDS screening cutoff may suggest early biological sensitivity associated with PPD vulnerability. Although the factors determining who develops PPD remain unclear, our findings may highlight the potential value of integrating OT response assessments with EPDS screening to improve early detection. Further, these findings suggest that OT dynamics may serve as a biological indicator of subtle emotional changes during the postpartum period.